2013
DOI: 10.1007/s13201-013-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Water quality index to determine the surface water quality of Sankey tank and Mallathahalli lake, Bangalore urban district, Karnataka, India

Abstract: The present work aims at assessing the water quality index (WQI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(70 citation statements)
references
References 14 publications
6
63
0
1
Order By: Relevance
“…The lower pH values have a tendency to make water corrosive, and higher pH value leads to taste grievance and harmful impact on the eyes and skin (Ravikumar et al 2013). pH value in groundwater samples ranging from 7.29 to 8.17, 7.33-8.45, and 6.29-7.20 during pre-monsoon, monsoon, and post-monsoon seasons, respectively, indicates the alkaline nature and slightly acidic in post-monsoon season.…”
Section: Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower pH values have a tendency to make water corrosive, and higher pH value leads to taste grievance and harmful impact on the eyes and skin (Ravikumar et al 2013). pH value in groundwater samples ranging from 7.29 to 8.17, 7.33-8.45, and 6.29-7.20 during pre-monsoon, monsoon, and post-monsoon seasons, respectively, indicates the alkaline nature and slightly acidic in post-monsoon season.…”
Section: Phmentioning
confidence: 99%
“…Total dissolved solids indicate the various types of minerals present in water in dissolved form consisting of calcium, magnesium, sodium, potassium, carbonates, bicarbonates, chlorides, sulfate, phosphate, silica, iron, and small amounts of organic matters (Gnanachandrasamy et al 2014;Ravikumar et al 2013). TDS in the study area varies from 817 to 4340 mg/L (pre-monsoon), 915 to 4243 mg/L (monsoon), and 1094 to 4346 mg/L (postmonsoon).…”
Section: Total Dissolved Solidsmentioning
confidence: 99%
“…Selvam et al (37) evaluated the water quality index of groundwater resources around the coastal city of Tuticorin in southern India and concluded that the groundwater quality was impaired by man-made activities. Ravikumar et al studied the water quality index to determine the quality of surface water of Mallathahalli Lake in India and showed that the lake water fell into the poor water category (38).…”
Section: Discussionmentioning
confidence: 99%
“…They regulate the urban climate (Benjamin, 1996) and also have a prominent effect on ground water quality and ground water table (Ravikumar, 2013). Lakes have environmental significance as sources of surface and ground water recharge, maintain nutrient and energy exchange with watersheds and air sheds and support diversified aquatic life.…”
Section: Introductionmentioning
confidence: 99%